Investigations into the post-translational modification and mechanism of isopenicillin N:acyl-CoA acyltransferase using electrospray mass spectrometry. - Aplin, RT; Baldwin, J; Roach, P; Robinson, C; Schofield, C (1993)
Electrospray mass spectrometry (e.s.m.s.) was used to confirm the position of the post-translational cleavage of the isopenicillin N:acyl-CoA acyltransferase preprotein to give the alpha- and beta-subunits. The e.s.m.s. studies suggested partial modification of the alpha-subunit in vivo by exogenously added substituted acetic acids. E.s.m.s. has also allowed the observation in vitro of the transfer of the acyl group from several acyl-CoAs to the beta-subunit. N.m.r. data for the CoA species have been deposited as Supplementary Publication SUP 500173 (2 pages) at the British Library Document Supply Centre (DSC), Boston Spa, Wetherby, West Yorkshire LS23 7BQ, from whom copies can be obtained on the terms indicated in Biochem. J. (1993) 289, 9.